Case studies in suburban sustainability - Garren, Sandra J.; Brinkmann, Robert, 1961- (University of Florida Press, 2020)
"The first volume to focus on suburbs and sustainability in the United States, this collection approaches the topic through regionally diverse case studies, showing that activism and leadership are currently advancing a strong sustainability agenda in regions many would have believed unlikely"--